Environmental and systemic challenges to delivering services for Aboriginal adults with a disability in Central Australia. Issue 20 (25th September 2021) - Gilroy, John; Dew, Angela; Barton, Rebecca; Ryall, Lee; Lincoln, Michelle; Taylor, Kerry; Jensen, Heather; Flood, Victoria; McRae, Kim
Abstract: Purpose: This two-year (2016–2018) study aimed to identify what a good life is for Aboriginal people with disability in remote Central Australia and how service providers can support them to achieve a good life. This paper presents the findings that relate to barriers to delivering services for Aboriginal people with disability. Methods: In-depth interviews and focus groups were held with Aboriginal people with disability and their carers aged at least 18 years from the Ngaanyatjarra Pitjantjatjara Yankunytjatjara (NPY) Lands and community organisations providing services there. The data were analysed using thematic analysis. Results: There were 109 participants, of whom 47 were workers in service provider organisations and 62 were Aboriginal people. From the data, barriers to delivering services to support Aboriginal people to live a good life and solutions to overcome the barriers, were identified and described under the headings of environmental barriers and systemic issues. Conclusions: We discuss the policy implications of these findings with regard to addressing Indigenous disadvantage and how governments, service providers, communities, and Aboriginal people with disability and their families can work in partnership to address these barriers. Implications for Rehabilitation: Indigenous people with disability living in remote and very remote communities experience significant access and equity barriers to culturally responsive services that enable them to live a socially and culturally engaged life. Localised government and service provider disability policy approaches in Indigenous communities need to focus on both environmental and systemic issues. Greater investment in local remote communities is required to build the capacity of Indigenous families to support Aboriginal people with a disability to live a culturally and socially included life.